2016
DOI: 10.1016/j.bbmt.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocyte Antigen-4 Down-Regulates T Helper 1 Cells by Increasing Expression of Signal Transducer and Activator of Transcription 3 in Acute Graft-versus-Host Disease

Abstract: Numerous previous studies have suggested that cytotoxic T lymphocyte antigen-4 (CTLA-4) plays an important role in acute graft-versus-host disease (GVHD). How CTLA-4 acts in regulating acute GVHD remains unknown, however. In the present study, we found that, compared with healthy controls, CTLA-4 plasma and relative mRNA levels in patients with acute GVHD were initially decreased and then markedly elevated after 28 days of treatment. CTLA-4 levels were higher in patients with grade I-II acute GVHD compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
3
2
0
Order By: Relevance
“…Meanwhile, the activation of T lymphocytes was enhanced, and the degree of apoptosis in T cells was decreased with increased secretions of IFN-γ and other cytokines. Increased levels of IFN-γ, IL-17 and IL-22, and decreased IL-4 levels were observed in the A and B groups, indicating an imbalance of Th1/17/22 and Th2 cells in the pathogenesis of GVHD, consistent with a previous study reporting that T cell activation was remarkably inhibited, with reduced levels of IFN-γ, IL-17 and IL-22 (19). From the in vitro results in the present study, it was indicated that TIRC7 upregulated the expression of CTLA-4, increased the activation of STAT3, inhibited the proliferation of T cells, promoted the apoptosis of T cells and decreased the secretion of cytokines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the activation of T lymphocytes was enhanced, and the degree of apoptosis in T cells was decreased with increased secretions of IFN-γ and other cytokines. Increased levels of IFN-γ, IL-17 and IL-22, and decreased IL-4 levels were observed in the A and B groups, indicating an imbalance of Th1/17/22 and Th2 cells in the pathogenesis of GVHD, consistent with a previous study reporting that T cell activation was remarkably inhibited, with reduced levels of IFN-γ, IL-17 and IL-22 (19). From the in vitro results in the present study, it was indicated that TIRC7 upregulated the expression of CTLA-4, increased the activation of STAT3, inhibited the proliferation of T cells, promoted the apoptosis of T cells and decreased the secretion of cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that CTLA-4 may play a negative role in the regulation of acute GVHD (6,7). The present study also demonstrated that CTLA-4 may be involved in the pathogenesis of acute GVHD, and that it may downregulate Th1 cell levels by increasing the expression of STAT3 in acute GVHD (19); meanwhile, other studies have reported that TIRC7 is the upstream regulatory molecule of CTLA-4 (9,11). Therefore, the present study hypothesized that both TIRC7 and CTLA-4 play important roles in acute GVHD, and that TIRC7 may regulate the expression of CTLA-4 in acute GVHD.…”
Section: Discussionsupporting
confidence: 71%
“…Stat3 was first examined in GVHD using a flow cytometry technique that was novel at the time, using antibodies to detect phosphorylation within cells. This study showed that Stat3 phosphorylation occurred during GVHD( 76 ), and these data were later confirmed ( 68 , 77 ). Interruption of Stat3 phosphorylation with a small molecule inhibitor reduced T cell proliferation and activation both in vivo and in vitro , and reduced GVHD severity ( 76 ).…”
Section: Transcription Factors Which May Separate Gvhd/gvlsupporting
confidence: 56%
“…The use of abatacept prior to HSCT is to modulate autologous activated T cells to control the underlying disease. Its use in the posttransplant phase could be beneficial both in controlling the remaining autologous T cells to reduce the risk of disease flare, but also to modulate allo-reactive donor T cells to reduce the risk of GVHD development ( 49 , 50 ). On the other hand, if the patient presents GVHD, such as case 2, the approach to slowly withdraw the immunosuppressant drug, or even switch to a Treg-sparing regimen such as sirolimus, can be considered.…”
Section: Discussionmentioning
confidence: 99%